PTSD and the politics of trauma in Israel : a nation on the couch - Friedman-Peleg, Keren, 1975- (University of Toronto Press, 2017)
"Post-Traumatic Stress Disorder, or PTSD, has long been defined as a mental trauma that solely affects the individual. However, against the backdrop of contemporary Israel, what role do families, health experts, donors, and the national community at large play in interpreting and responding to this individualized trauma? In PTSD and the Politics of Trauma in Israel, Keren Friedman-Peleg sheds light on a new way of speaking about mental vulnerability and national belonging in contemporary Israel. Based on ethnographic fieldwork conducted at The Israel Center for Victims of Terror and War and The Israel Trauma Coalition between 2004 and 2009, Friedman-Peleg's rich ethnographic study challenges the traditional and limited definitions of trauma. In doing so, she exposes how these clinical definitions have been transformed into new categories of identity, thereby raising new tensions, new dynamics of power, and new forms of dialogue."--